Analisis Kemampuan Berpikir Matematis Siswa SMA kota Sorong terhadap Butir Soal dengan Graded Response Model - Kahar, Muhammad Syahrul (Universitas Islam Negeri Raden Intan Lampung, 2017)
This research aims to know the level of mathematical thinking ability of students by using scored model Graded Response Model (GRM). The subject here is the students of Class XI IPA 1 SMA Negeri 3 Sorong the 2016/2017 academic year, which amounted to 38 students with 22 students are male and 16 female students. This research is a descriptive research experiment. The results of this study indicate that the scored model GRM is effective in analyzing the ability of mathematical thinking of students. The effectiveness is shown an increase in student learning outcomes grade XI IPA 1 SMA Negeri 3 Kota Sorong, where the average grade results visible increase of 56.7 until 78, and the value of the completeness students improved significantly, and student learning outcomes were shown in graded contents relevance criteria students with score 4 there are 18 students (47.37%), while the relevance of the contents with a score of 1 there are 4 students (10.53%). From the criteria of completeness students who achieve complete answers by a score of 4, there are 1 students (2.64%), and the answers are far from finished with a score of 1 there were 7 students (19.52%). Then to organizing criteria, students are working on a very systematic, there are 8 students (21.05%), and organizing with not systematically there are 10 students (26.32%).Penelitian ini bertujuan untuk mengetahui tingkat kemampuan berpikir matematis siswa dengan menggunakan model penyekoran Graded Response Model (GRM). Subjek penelitian disini adalah siswa kelas XI IPA 1 SMA Negeri 3 Kota Sorong tahun ajaran 2016/2017, yang berjumlah 38 siswa dengan 22 siswa laki-laki dan 16 siswa perempuan. Penelitian ini adalah penelitian eksperimen yang bersifat Deskriptif. Hasil penelitian ini menunjukkan bahwa model penyekoran GRM ini efektif dalam menganalisis kemampuan berpikir matematis siswa. Keefektifan tersebut terlihat adanya peningkatan hasil belajar siswa kelas XI IPA 1 SMA Negeri 3 Kota Sorong, dimana hasil rerata kelas terlihat meningkat dari 56,7 hingga 78, dan nilai ketuntasan siswa meningkat secara signifikan, dan hasil belajar siswa dilihat secara graded dengan kriteria relevansi isi dengan skor 4 terdapat 18 siswa (47,37%), sementara relevansi isi dengan skor 1 terdapat 4 siswa (10,53%). Dari kriteria ketuntasan siswa yang mencapai jawaban tuntas dengan skor 4 terdapat 1 siswa (2,64%), dan jawaban jauh dari tuntas dengan skor 1 terdapat 7 siswa (19,52%). Kemudian untuk kriteria pengorganisasian, siswa mengerjakan dengan sangat sistematis terdapat 8 siswa (21,05%), dan pengorganisasian dengan tidak sistematis terdapat 10 siswa (26,32%).